2018
DOI: 10.14302/issn.2639-3166.jar-18-2084
|View full text |Cite
|
Sign up to set email alerts
|

NIRS Footprint of Bio-Fertilizers from Hay Litter-Bags

Abstract: The biofertilization of cropsusing microbial biota in the soil (MBS) is a modern practice that is used to sustain fertility. MBS agents can promote the yield and health of crops, by luxuriating in the shoot as well as in the root systems. Farmers devoted to systematic MBS fertilization are creating a “Symbiotic” (S) form of agriculture, which offers a greater advantage of resilience than Conventional (C) or organic farming. Since MBS is involved in organic matter degradation, hay-litter-bag probes can be used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
(17 reference statements)
1
10
1
Order By: Relevance
“…In the first experiments conducted to formalize the litter-bag method 18 , the eight litter-bag calibration studies, devoid of yield results, showed an average sensitivity of 62% for C and 71% for S, values that now result to clearly be below the range of sensitivity expressed in the present work with reference to intensive corn fields.…”
Section: Negative Positivecontrasting
confidence: 55%
See 2 more Smart Citations
“…In the first experiments conducted to formalize the litter-bag method 18 , the eight litter-bag calibration studies, devoid of yield results, showed an average sensitivity of 62% for C and 71% for S, values that now result to clearly be below the range of sensitivity expressed in the present work with reference to intensive corn fields.…”
Section: Negative Positivecontrasting
confidence: 55%
“…Three recently published rapid methods, namely the NIRS-litter-bag technique 18 , raw foliar pH 19,20,21 and foliar NIR-SCiO Tomoscopy 20 , have been used together for the first time for modeling purposes, thanks to the availability of a new smart-NIR device, which has been utilized for the leaves of Sorghum sudanensis but also for live rabbits 22 . The results from three calibration experiments conducted in 2018 were elaborated to formulate a model for a symbiotic corn yield.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three recently published rapid methods, namely the NIRS-litter-bag technique 13 , the raw foliar pH 14,15,16 and foliar NIR-Tomoscopy 17 , have been used together, in a holistic model, for a symbiotic corn yield production 4 . The aim of this study has been to investigate the quality of symbiotic corn.…”
Section: Methodsmentioning
confidence: 99%
“…However, there is still a lack of rapid measurement techniques that can be used to assess the microbial status of cultivated soils. The integrated use of NIRS and litterbag techniques could be a functional and rapid solution, as demonstrated by the fact that a change caused by a biofertilizer is reflected in the biochemical functioning mechanisms, and that such a change can be easily testified 8 . The coupled use of these two techniques (intended as a quality evolution of litterbags swamps and not as mass decay), can be modeled as a valid fingerprinting of the studied field conditions, a process that results in data validation and predictive models.…”
Section: The Use Of Litterbags Is a Technique That Hasmentioning
confidence: 99%